Pengembangan Karir Dosen Melalui Tri Dharma Perguruan Tinggi Muhammadiyah Bojonegoro - Maulidyah Amalina Rizqi; Elok Vilantika (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
University Education Education and teaching, research and development, and community service make up the three pillars of Tri Dharma. Typically, each college simply concentrates on education and teaching in order to make the other two elements slightly better. Bojonegoro Regency is home to the Muhammadiyah College of Tarbiyah (STIT) Muhammadiyah Bojonegoro. The tri dharma is still not being implemented to its full potential, particularly in terms of research and community service. It is intended that by providing this service, the number and quality of research and service will both rise. The mentorship and workshop strategy is employed in this service. This exercise starts with recognizing the issues that partners are facing, which is followed by sharing sessions. To ensure that agency activities adhere to the guidelines set forth by the Ministry of Education and Culture, agencies must encourage all lecturers to practice the tri dharma properly. To transform the culture, nevertheless, considerable effort must be put into encouraging all levels of the existing human resources to abide by the regulations established in accordance with SN DIKTI.